UN and lethal autonomous weapons: a Gordian knot of international humanitarian law - HONCHARUK Дмитро (Ius Modernum, 2025)
The rapid militarization of artificial intelligence and the emergence of lethal autonomous weapon systems (LAWS) generate a complex of legal, ethical, and security challenges – ranging from uncertainty of accountability to risks of algorithmic bias and cyber interference; the United Nations is the central platform for developing global approaches, particularly within the framework of the CCW/GGE. Despite the absence of consensus on a legally binding instrument for a decade, UN activities institutionalize ethical benchmarks and political principles – such as human-centeredness, responsibility, and "meaningful human control" – thereby shaping the normative boundaries of acceptability for LAWS. This study combines two analytical perspectives: (1) the evolution of norm-setting within the CCW/GGE (as lex specialis) and the 11 Guiding Principles; and (2) the broader UNGA discourse on science, technology, and security (A/79/224), which embeds LAWS into the general agenda of "digital norms". The analysis of the GGE’s work and UNGA resolutions indicates that a consensus has emerged around a two-tier regulatory model: firstly, states should assume negative obligations – to prohibit categories of LAWS that are incompatible with international humanitarian law and the principle of meaningful human control (in particular, systems capable of autonomously targeting humans). Secondly, for other systems with elements of autonomy, positive obligations are necessary — to ensure human control and accountability at all stages of the weapons life cycle, to conduct legal reviews, and to implement technical and organizational guarantees of transparency and reliability. The UN is creating a "regulatory field of attraction" for a future LAWS treaty; however, maintaining political divergences and the consensus-based CCW procedure requires transforming principles into clear legal norms in close interaction among states, international organizations, and civil society.